Processamento de hidroxiapatita por microondas: síntese de pós e sinterização de peças - Duarte, Eden Batista (2009)
Bioceramic are substances or combination of substances which has some clinical applicability and can be used for treating or replacing any tissue, organ or function of the body. They are chemically stable and have almost no adverse biological effects. The most widely used bioceramics for tissue reconstitution are calcium phosphate based bioceramics having Ca/P ratio changing from 0.5 to 2.0, which leads to diferent phases. The most important phase is hydroxyapatite due to its chemical composition, which is similar to that of hard tissues. Hydroxyapatite can be obtained by different mechanisms such as wet methods and solid-state reactions. In this study, apatite bioceramics were obtained from solid-state reaction by Microwave Irradiation, using calcium phosphate (CaHPO4) and calcium hydroxide [Ca(OH)2]. The powders obtained were heat treated at 850°C and 1050°C and characterized by X-Ray Diffraction (XRD), Fourier Transform Infrared (FTIR) Spectroscopy, Thermal Gravimetric Analysis (TGA) and Scanning Electron Microscope (SEM). The predominant phases identified were hydroxyapatite and β-tricalcium phosphate. The powders were uniaxially pressed in cylindrical dyes and sintered at 1200°C for 1hour. Final microstructure presented the hydroxyapatite (HA) phase